1999
DOI: 10.1007/978-94-011-4780-4_69
|View full text |Cite
|
Sign up to set email alerts
|

Jets from Time-Dependent Accretion Flows Onto a Black Hole

Abstract: We investigate time-dependent inviscid hydrodynamical accretion flows onto a black hole using numerical simulations. We consider the accretion that consists of hot tenuous gas with low specific angular momentum and cold dense gas with high specific angular momentum. The former accretes continuously and the latter highly intermittently as blobs. The high specific angular momentum gas blobs bounce at the centrifugal barrier and create shock waves. The low specific angular momentum gas is heated at the shock fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 16 publications
0
38
2
Order By: Relevance
“…However, even with the simple inviscid hypothesis, the stability of the shock is not fully understood. In the isothermal limit, Nakayama (1992) introduced a global instability between a sonic point and a shock, and found the criterion that ‘post‐shock acceleration causes instability’, which was confirmed by the simulations of Nobuta & Hanawa (1994). Moreover, Nakayama (1994) investigated this instability in an adiabatic flow and claimed that such a criterion is also correct unless the shock is extremely strong.…”
Section: Introductionmentioning
confidence: 93%
“…However, even with the simple inviscid hypothesis, the stability of the shock is not fully understood. In the isothermal limit, Nakayama (1992) introduced a global instability between a sonic point and a shock, and found the criterion that ‘post‐shock acceleration causes instability’, which was confirmed by the simulations of Nobuta & Hanawa (1994). Moreover, Nakayama (1994) investigated this instability in an adiabatic flow and claimed that such a criterion is also correct unless the shock is extremely strong.…”
Section: Introductionmentioning
confidence: 93%
“…Subsequently, Chakrabarti (1990b, hereafter C90b) showed that inclusion of viscosity reduces the region of the parameter space in that, at a sufficiently high viscosity, the Rankine–Hugoniot conditions which must be satisfied at a steady shock are not satisfied anywhere in the flow. The existence of standing shocks in sub‐Keplerian inviscid accretion discs has been tested independently by several groups since then (Nobuta & Hanawa 1994; Yang & Kafatos 1995; Lu & Yuan 1997). Numerical simulations have also been carried out with several independent codes such as smoothed particle hydrodynamics (SPH) and total variation diminishing (TVD) and distinct standing shocks were found exactly at the predicted locations (Chakrabarti & Molteni 1993; Molteni, Ryu & Chakrabarti 1996b).…”
Section: Introductionmentioning
confidence: 99%
“…As the flow moves closer to the black hole, and the centrifugal force grows, at some point, the supersonic flow may become subsonic at the shock front (C89; Nobuta & Hanawa 1994). It becomes supersonic again after passing through the inner critical point (C89).…”
Section: Governing Equations and Shock Conditionsmentioning
confidence: 99%